Registered Medical Practitioners: Perception of Professional Secrecy (Journal of Forensic Medicine & Toxicology, 2025)
Confidentiality is the foundation of the physician-patient relationship, safeguarded by ethical and legal guidelines glob ally. This study evaluates Registered Medical Practitioners’ (RMPs) awareness and perception of professional secrecy,  which is crucial for preventing legal and ethical violations. This cross-sectional survey-based study was conducted at a  tertiary health care teaching hospital, which included 342 RMPs from various specialties. The participants’ knowledge  was assessed using a standardized questionnaire, with responses categorized based on accuracy. The findings indicated  that while RMPs were well-informed about confidentiality in cases of notifiable diseases (75.43%), their awareness dimin ished in complex situations such as disclosing patient information to employers, insurers, or in court (71.92% to 60.52%  incorrect responses). RMPs showed better understanding when the patient’s guardian or hostel warden was involved  (61.11%) but lacked knowledge in areas such as the disclosure of information without patient consent for non-commu nicable diseases. The study identified gaps in the legal and ethical frameworks guiding professional secrecy, highlighting  the need for enhanced training in medical jurisprudence during medical education. Recommendations include manda tory medical jurisprudence training during both undergraduate and postgraduate education to address these knowledge  gaps. The study underscores the importance of continuous education to ensure RMPs comply with ethical standards and  legal requirements, ultimately safeguarding patient privacy and public health.
Keywords: Registered Medical Practitioner; Professional Secrecy; Confidentiality; Doctor-Patient relationship; Medical Ethics